Pharmacokinetics and pharmacodynamics of insulin lispro 25 versus the original preparation (Humalog®25) in Chinese healthy male volunteers - Zhu, Mingxue; Chen, Yuan; Wan, Lei; Li, Zhongping; Pu, Junliang; Tang, Chengyong (Frontiers in Pharmacology, 2025)
Background: There are approximately 537 million adults with diabetes worldwide, and insulin still plays an important role in its treatment. However, the long-term use of insulin imposes a significant financial burden on patients. This study aims to explore the pharmacokinetic (PK)/ pharmacodynamic (PD) parameters of generic premixed insulin lispro 25 (25% insulin lispro and 75% protamine zinc lispro) and evaluate the bio-equivalence between generic and brand-name preparations to reduce medical costs while ensuring the effectiveness and safety of treatment.Research design and method: This is a single-center, randomized, open-label, two-period, crossover study. This study recruited 52 healthy volunteers and randomly divided them into two sequences to receive either the test (T) preparation or the reference (R) preparation in each period (Chinese Drug Trial Identifier: CTR20202288, URL: http://www.chinadrugtrials.org.cn). The C-peptide and plasma concentration of lispro 25 were analyzed using ELISA and high-performance liquid chromatography, respectively. A euglycemic clamp was used to measure the glucose infusion rate (GIR). The main PK parameters (AUC0-t and Cmax) and PD parameters (GIRmax and GIRAUC0-t) and the evaluation of bioequivalence were calculated using WinNonlin 8.3.1.Results: The quality of the clamp was approved by stable blood glucose and inhibited C-peptide levels. For PK parameters, the Cmax values of the T and R preparations were 1.40 ± 0.452 and 1.36 ± 0.418 ng·mL-1, respectively, and the AUC0–24h values were 497 ± 107 and 510 ± 86.2 ng h·mL-1, respectively. For PD parameters, GIRmax values were 4.47 ± 2.12 and 4.12 ± 1.81 mg kg·min-1, and AUCGIR0–24h values were 2,994 ± 1,232 and 2,994 ± 941 mg h·kg·min-1 for T and R, respectively. The 90% confidence intervals (CIs) for the geometric mean ratio (test/reference) of the main PK parameters (AUC0-t and Cmax) and PD parameters (GIRmax and GIRAUC0-t) in both cohorts were within the range of 80%–125%. Furthermore, there was no significant hypoglycemia and serious adverse events (SAEs) observed in this study.Conclusion: Bio-equivalence between insulin lispro (R) (Humalog®25) and insulin lispro (T) was demonstrated, with both showing good tolerance in healthy Chinese volunteers. The results provide evidence supporting the interchangeability of different drug formulations and offer more options for clinical drug use.